(untitled) (Lex Scientia Law Review, 2025)
The prevalence of hoaxes in Indonesia is not a new phenomenon. Over the past three years, there has been a consistent increase in the dissemination of hoaxes across various platforms in the country. Furthermore, with the onset of the pandemic, the spread of hoaxes related to Covid-19 has become particularly rampant. In 2021 itself, the Ministry of Communications and Informatics identified and debunked a total of 723 hoaxes pertaining to Covid-19. This research paper aims to examine the current state of hoax dissemination in Indonesia and identify the key factors contributing to their spread. The study adopts a normative legal research approach, drawing on data derived from books, journals, relevant laws, and regulations. The findings reveal that social media platforms play a significant role in the proliferation of hoaxes throughout Indonesia. The presence of numerous anonymous or fake accounts facilitates the easy dissemination of hoaxes via social media. Moreover, the lack of due diligence in verifying and fact-checking information creates a loophole that allows hoaxes to circulate within the community. In order to address this issue effectively, it is crucial to implement measures that target the root causes of hoax dissemination. This includes the development of stricter regulations and enforcement mechanisms to combat the creation and spread of hoaxes, particularly on social media platforms. By comprehensively understanding the dynamics and factors influencing the spread of hoaxes in Indonesia, policymakers, law enforcement agencies, and the general public can work together to combat this pressing issue.